Complexometric Determination of Copper in Pharmaceutical Samples Using Hydroxytriazenes - Sharma, J.C.; Upadhyay, Mishika; Jain, C.P.; Dashora, Rekha (Asian Journal of Chemistry, 2010)
The present paper describes complexometric determination of Cu(II) using three hydroxytriazenes as metallochromic indicators in three drugs Tamra-bhasm-I, Tamra-bhasm- II and Tamra-bhasm-III. The hydroxytriazenes used were 3-hydroxy-3-methyl-1-psulphonamidophenyl triazene (HMSPT), 3-hydroxy-3-phenyl-1-p-chlorophenyl triazene (HPpCPT) and 3-hydroxy-3-phenyl-1-m-chlorophenyl triazene (HPmCPT), respectively.